Insulin degludec/liraglutide (IDegLira) for the treatment of type 2 diabetes - Gough, Stephen CL (Expert Rev Endocrinol Metab, 2016)
The progressive nature of type 2 diabetes necessitates that treatment is intensified as the disease advances. Several studies have shown that basal insulin and glucagon-like peptide-1 receptor agonists (GLP-1RAs) can be used in combination to successfully improve glycemic control and this combination is increasingly being considered as an alternative to intensification with prandial insulin. Insulin degludec/liraglutide (IDegLira) is the first fixed-ratio combination of a basal insulin and a GLP-1RA in a single formulation. Here we consider the benefits and potential limitations of such a combination, focusing on the unique modes of action of insulin degludec and the once-daily GLP-1RA liraglutide. IDegLira offers an efficacious combination therapy (mean end-of-trial HbA(1c) was 6.4–6.9% across the five completed Phase 3 trials), which was well-tolerated in clinical trials. The complementary modes of action resulted in a low rate of hypoglycemia and no weight gain in insulin-treated patients. As a once-daily injection with effects on both fasting and post prandial hyperglycemia, IDegLira has the potential to help many patients reach glycemic target (60–81% of patients achieved HbA(1c) <7% in clinical trials).